Activation of pregnane X receptor inhibits experimental dermal fibrosis. Issue 4 (4th January 2013) - Beyer, Christian; Skapenko, Alla; Distler, Alfiya; Dees, Clara; Reichert, Helena; Munoz, Louis; Leipe, Jan; Schulze-Koops, Hendrik; Distler, Oliver; Schett, Georg; Distler, Jörg H W
Abstract : Objective: To assess the antifibrotic effects of pregnane X receptors (PXRs) in experimental dermal fibrosis. Methods: The antifibrotic effects of PXR activation by 5-pregnen-3β-ol-20-one-16α-carbonitrile (PCN) were studied in the bleomycin model for prevention of dermal fibrosis and the modified bleomycin model for the treatment of established bleomycin-induced dermal fibrosis. Activation of canonical transforming growth factor (TGF)β signalling was analysed by immunofluorescence staining for phosphorylated smads. The antifibrotic effects of PXR activation were further studied in murine fibroblasts and murine T cells under Th2 conditions. In the T cell experiments, synthesis of the profibrotic cytokines, interleukin (IL)-4 and IL-13, was assessed by quantitative PCR, and IL-13 levels in the murine skin were determined by multiplex bead array technology. Results: Activation of PXR effectively inhibited the development of bleomycin-induced dermal fibrosis and induced the regression of established dermal fibrosis as assessed by skin thickening, hydroxyproline content and myofibroblasts. Reduced levels of phosphorylated smad2 and smad3 suggested that the antifibrotic effects of PXRs were mediated by inhibition of canonical TGFβ signalling. While PXR activation appeared to have no direct effects on fibroblasts, it potently inhibited the release of the profibrotic cytokine, IL-13, from Th2 cells. Consistent with these findings, IL-13 levels were reduced in bleomycin-challenged murine skin upon PXR activation. Conclusions: Our findings demonstrate a novel antifibrotic role for PXRs in inflammatory dermal fibrosis. The antifibrotic effects of PXRs appear to be indirect: PXR activation reduces the release of the Th2 cytokine, IL-13, from T cells resulting in decreased canonical TGFβ signalling.